2022
DOI: 10.3847/2041-8213/ac8c8f
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Interaction with the Spacecraft Plasma Wake Generates Plasma Waves Close to the Electron Cyclotron Frequency in the Near-Sun Solar Wind

Abstract: Prior observations of the near-Sun solar wind (sunward of 0.25 au) identified frequent, intense plasma waves near the local electron cyclotron frequency (f ce), and its harmonics. In this Letter, it is shown that near-f ce wave properties are consistent with generation via interaction between the observing spacecraft’s ion wake and the ambient plasma and magnetic fields. This result implies that many observed near-f ce waves are not intrinsic to the unobstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similar structures with magnetic field magnitude depletion were observed in the vicinity of the Earth bow shock by the four MMS spacecraft with hightime resolution electron measurements aboard (Ahmadi et al 2018), and these observations nicely confirm our assumptions highlighting the trapped hot electron population. Such distribution (with the proper plasma temperature) can guide the generation of whistler waves propagating along and opposite the background magnetic field through the cyclotron instability (Drake et al 2015;Agapitov et al 2018;Ahmadi et al 2018;Malaspina et al 2022;Tigik et al 2022). For the magnetic hole, which is in the rest with respect to the background core plasma, i.e., propagating with the bulk solar wind velocity, such a distribution is shown schematically in Figure 12(e).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar structures with magnetic field magnitude depletion were observed in the vicinity of the Earth bow shock by the four MMS spacecraft with hightime resolution electron measurements aboard (Ahmadi et al 2018), and these observations nicely confirm our assumptions highlighting the trapped hot electron population. Such distribution (with the proper plasma temperature) can guide the generation of whistler waves propagating along and opposite the background magnetic field through the cyclotron instability (Drake et al 2015;Agapitov et al 2018;Ahmadi et al 2018;Malaspina et al 2022;Tigik et al 2022). For the magnetic hole, which is in the rest with respect to the background core plasma, i.e., propagating with the bulk solar wind velocity, such a distribution is shown schematically in Figure 12(e).…”
Section: Discussionmentioning
confidence: 99%
“…These periods of whistler wave activity are interspersed with higher frequency electron Bernstein modes in the range of f ce and its harmonics (Malaspina et al 2020). Recent work has demonstrated that the observed electron Bernstein modes are most likely generated by the interaction between the solar wind and the Parker Solar Probe spacecraft wake (Malaspina et al 2022;Tigik et al 2022). Nonetheless, electron Bernstein waves are found to preferentially occur in regions of exceptionally lowamplitude magnetic turbulence, termed quiescent regions (Short et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Because the antennas on the Parker Solar Probe are not much larger than the spacecraft body, it is possible, under certain geometric conditions, that one or more antennas might be in the vehicle wake to produce a spurious wave electric field. In fact, cases of spurious whistler waves have been reported [Malaspina et al, 2022]. To test for this possibility, Figure A2 gives the solar wind speed (panel (c)), the angle of the magnetic field from the Z-direction (panel (d)), the plasma density (panel (e)), and the ion temperature (panel f)).…”
Section: Appendixmentioning
confidence: 99%
“…If a 15 minute interval has 10 or fewer wave detections, it is removed from consideration. The resulting wave identifications are also examined by eye to remove wake-generated waves near the local electron cyclotron frequency (Tigik et al 2022;Malaspina et al 2022a). The wake-generated waves are readily identified as near-harmonic bands of power at an approximately constant frequency close to the electron cyclotron frequency.…”
Section: Wave Identificationmentioning
confidence: 99%